In silico discovery of diagnostic/vaccine candidate antigenic epitopes and a multi-epitope peptide vaccine (NaeVac) design for the brain-eating amoeba Naegleria fowleri causing human meningitis - Koeseoglu, Ahmet Efe; Ozgul, Filiz; Isiksal, Elif Naz; Seflekci, Yusuf; Tulumen, Deniz; Ozgultekin, Buminhan; Koseoglu, Gulsum Deniz; Ozyigit, Sena; Ihlamur, Murat; Merdan, Yagmur Ekenoglu (ELSEVIER, 2024)
Naegleria fowleri, the brain-eating amoeba, is a free-living amoeboflagellate with three different life cycles (trophozoite, flagellated, and cyst) that lives in a variety of habitats around the world including warm freshwater and soil. It causes a disease called naegleriasis leading meningitis and primary amoebic meningoencephalitis (PAM) in humans. N. fowleri is transmitted through contaminated water sources such as insufficiently chlorinated swimming pool water or contaminated tap water, and swimmers are at risk. N. fowleri is found all over the world, and most infections were reported in both developed and developing countries with high mortality rates and serious clinical findings. Until now, there is no FDA approved vaccine and early diagnosis is urgent against this pathogen. In this study, by analyzing the N. fowleri vaccine candidate proteins (Mp2CL5, Nfa1, Nf314, proNP-A and proNP-B), it was aimed to discover diagnostic/vaccine candidate epitopes and to design a multi-epitope peptide vaccine against this pathogen. After the in silico evaluation, three prominent diagnostic/vaccine candidate epitopes (EAKDSK, LLPHIRILVY, and FYAKLLPHIRILVYS) with the highest antigenicities were discovered and a potentially highly immunogenic/antigenic multi-epitope peptide vaccine (NaeVac) was designed against the brain-eating amoeba N. fowleri causing human meningitis.
Keywords: Naegleria fowleri; Brain-eating amoeba; Diagnostic; Vaccine; In silico; PROTEIN-STRUCTURE; WEB SERVER; PREDICTION; MODEL; GENE; IDENTIFICATION; EXPRESSION; PROTECTION; ANTIBODIES; BIOLOGY; Genetics & Heredity